Pre-service Teachers' Perceptions on the Use of Mobile Applications for language Learning - Eka Ananda Putri; Dadang Danugiri; Fauzi Miftakh (Universitas Muhammadiyah Enrekang, 2021)
Learning language nowadays can be done by many ways including using mobile technology or mobile phone and its applications. Learning uses mobile applications not only can be done by using app-based language learning, but also using general application. This descriptive case study was used to investigate and find out about pre-service teachers’ levels and perceptions on the use of mobile applications for language learning. The data from six pre-service teachers were collected by using semi-structured interviews and questionnaire. The result showed that all of pre-service teachers have different levels of using mobile applications for language learning based on their purposes, challenges and experiences. In addition, most of pre-service teachers have positive perceptions on the use of mobile application for their language learning regarding on aim-mobile technologies fit, appropriate of branch, and forms of m-learning application and tools’ sufficient adequacy of communication, the findings revealed that (1) mobile applications remove the limitation of time and space; (2) mobile applications are reliable for personal use; and (3) course materials could be sent to students via mobile applications. In conclusion, the use of mobile applications for language learning are helpful for pre-service teachers.